Pengaruh Promosi Media Sosial Dan Word Of Mouth Terhadap Keputusan Pembelian Pada Dto Thaitea Bengkulu - Tri seira Febrisa; Ahmad Soleh; Nurzam Trisna (UNIVED Press, 2023)
This study aims to analyze how big the impact of a promotion through social media and word of mouth on consumer purchasing decisions at DTO Thaitea Bengkulu, either simultaneously or simultaneously. The factors that will be discussed and are factors that have a very large influence on changes in the purchasing decision variables in this study are social media variables and word of mouth variables. The population in this study are consumers who have ever drank DTO Thaitea Bengkulu products, samples taken as many as 96 people. The data collection technique was taken by the institution in the form of questionnaires and the research analysis method used multiple linear regression, determination test and hypothesis testing. The conclusion of this study is that promotion through social media and word of mouth has a positive and significant impact on purchasing decisions for DTO Thaitea Bengkulu beverage products.